Synthesis of copaiba (Copaifera officinalis) oil nanoemulsion and the potential against Zika virus: An in vitro study - Carvalho, Tamara [UNESP]; Landim, Marcela Guimarães; Lima, Maria Letícia Duarte [UNESP]; Bittar, Cíntia [UNESP]; de Araújo Oliveira Faria, Beatriz Carvalho; Rahal, Paula [UNESP]; de Lima, Milena Campelo Freitas; da Veiga, Valdir Florêncio; Joanitti, Graziella Anselmo; Calmon, Marilia Freitas [UNESP] (Public Library of Science (PLoS), 2023)
Zika virus (ZIKV) has spread all over the world since its major outbreak in 2015. This infection has been recognized as a major global health issue due to the neurological complications related to ZIKV infection, such as Guillain–Barré Syndrome and Zika virus Congenital Syndrome. Currently, there are no vaccines or specific treatments for ZIKV infection, which makes the development of specific therapies for its treatment very important. Several studies have been developed to analyze the potential of compounds against ZIKV, with the aim of finding new promising treatments. Herein, we evaluate the ability of a copaiba (Copaifera officinalis) oil nanoemulsion (CNE) to inhibit ZIKV. First, the highest non-cytotoxic concentration of 180 μg/mL was chosen since this concentration maintains 80% cell viability up to 96h after treatment with CNE in VERO cells resulted from MTT assay. The intracellular uptake assay was performed, and confirmed the internalization of the nanoemulsion in cells at all times analyzed. VERO cells were infected with ZIKV and simultaneously treated with CNE and the nanoformulation without oil (ENE) at the highest non-toxic concentration. The results evaluated by plaque assay revealed a viral inhibition of 80% for CNE and 70% for ENE. A dose-dependence assay revealed that the CNE treatment demonstrated a dose-dependent response in the viral RNA levels, whereas all ENE tested concentrations exhibited a similar degree of reduction. Taken together, our results suggest CNE as a promising nano-sized platform to be further studied for antiviral treatments.